Incentive-compatible elicitation of quantiles - Nicholas M. Kiefer (Cornell University, Center for Analytical Economics (CAE), 2009)
Incorporation of expert information in inference or decision settings is often important, especially in cases where data are unavailable, costly or unreliable. One approach is to elicit prior quantiles from an expert and then to fit these to a statistical distribution and proceed according to Bayes rule. An incentive-compatible elicitation method using an external randomization is available.
Keywords: 330; Bayesian inference; mechanism design; prior assessment